PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN SERTA DAMPAKNYA PADA LOYALITAS KONSUMEN WEDDING ORGANIZER DI KOTA PRABUMULIH - Maharani Purnama, Putri (Universitas muhammadiyah palembang, 2018)
Purpose: This study aimed to determine the effect of service quality andprice to customer satisfaction and its impact on consumer loyality in the cityPrabumulih wedding organizer. Formulation of the problem is whether thereis influence service quality and price to customer satisfaction and its impacton consumer loyalty Prabumulih wedding organizer in the city?Design/Methodelogy/Approach: The data used in this study are primary data89 respondent reply. Models analysis used analysis and by testing thevalidity and reliability of instruments. Test charactistics data that is test ofnormality and linearity test. Test model consist of multicolinearity test andheterokesdatisitas test.Implications: The test results of path analysis showed that there werepositive and significant impact variable quality of service significantlyinfluence consumer satisfaction 0,000. Price variables significantly influenceconsumer satisfaction 0,000. Variable service quality signifintly consumerloyalty 0,000. Price variables dont have significantly influence consumerloyality 0,205. and Variable customer satisfaction dont have significantlyinfluence consumer loyalty 0,188.Findings: Their suitability to the theory and there is a match and supportprevious research. Increased service quality, price and customerssatisfaction and customer loyality.